PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA HOSTEL HARION BANDAR LAMPUNG - Budi, Hengki Setiya; Winata, Andri (Jurnal Manajemen Magister Darmajaya, 2018)
Harion Hostel Bandar Lampung as located on Jalan Pulau Batam No. 5 Bandar Lampung. Harion Hostel has several room types i.e: Single Standard, Superior, Deluxe, and Deluxe Double / Twin. The objective of the study wuse to lenau simultaneously and partially the impact of the price and service quality on customer satisfaction. This study used quantitative and associative method, to determine the relationship between two variables or more, and it has a causal relationship. Based on this research, F count test results is 44.820 > 3.09, this shows the price and service quality affects customer satisfaction. R square Determination coefficient value is 0.48. This means, 48 % of costumer’s satisfaction variable can be explained by The Price and Service Quality Factors, while the other remaining 52 % of customer satisfaction are explained by other variables. Based on The t-test, the price affects customer satisfaction with value of t-count is 9.494. And Service Quality didn’t affect the consumer’s satisfaction with value of t count is 0.205.Keywords — Price, Service Quality, Customer Satisfaction